Brain preparedness: The proactive role of the cortisol awakening response in hippocampal-prefrontal functional interactions. (October 2021) - Xiong, Bingsen; Chen, Changming; Tian, Yanqiu; Zhang, Shouwen; Liu, Chao; Evans, Tanya M.; Fernández, Guillén; Wu, Jianhui; Qin, Shaozheng
Graphical abstract: Highlights: A prospective design reveals the proactive role of CAR in human brain function. CAR promotes brain preparedness via improved prefrontal and hippocampal efficiency. CAR-related local effect is linked to enhancing prefrontal-hippocampal interaction. Pharmacologically suppressed CAR proves a causal link of CAR to brain preparedness. Abstract: Upon awakening from nighttime sleep, the stress hormone cortisol in humans exhibits a robust rise within thirty to forty-five minutes. This cortisol awakening response (CAR), a crucial point of reference within the healthy cortisol circadian rhythm, has been linked to various psychological, psychiatric and health-related conditions. The CAR is thought to prepare the brain for anticipated challenges of the upcoming day to maintain one's homeostasis and promote adaptive responses. Using brain imaging with a prospective design and pharmacological manipulation, we investigate the neurobiological mechanisms underlying this preparation function of the CAR across two studies. In Study 1, a robust CAR is predictive of less hippocampal and prefrontal activity, though enhanced functional coupling between those regions during a demanding task hours later in the afternoon. Reduced prefrontal activity is in turn linked to better working memory performance, implicating that the CAR proactively promotes brain preparedness based on improved neurocognitive efficiency. In Study 2, pharmacologically suppressed CAR using Dexamethasone mirrors this proactive effect, which further causes a selective reduction of prefrontal top-down functional modulation over hippocampal activity. These findings establish a causal link between the CAR and its proactive role in optimizing functional brain networks involved in neuroendocrine control, executive function and memory.